EFFICIENT USE OF WATER IN THE KHOREZM OASIS - MATYAKUBOV BAKHTIYAR SHAMURATOVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article provides information on the efficient use of water resources for the development of cotton irrigation regime, as well as on the identification and implementation of water-saving irrigation technologies and efficient use. The determination of cotton irrigation regime was carried out on the basis of the field experience scheme. Moreover, information on the water productivity used to obtain the maximum yield of cotton is given and the waterbalance of the cotton field compiled.